2022
DOI: 10.1073/pnas.2116220119
|View full text |Cite
|
Sign up to set email alerts
|

PROX1 transcription factor controls rhabdomyosarcoma growth, stemness, myogenic properties and therapeutic targets

Abstract: Rhabdomyosarcoma (RMS) is an aggressive pediatric soft-tissue cancer with features of skeletal muscle. Because of poor survival of RMS patients and severe long-term side effects of RMS therapies, alternative RMS therapies are urgently needed. Here we show that the prospero-related homeobox 1 (PROX1) transcription factor is highly expressed in RMS tumors regardless of their cell type of origin. We demonstrate that PROX1 is needed for RMS cell clonogenicity, growth and tumor formation. PROX1 gene silencing repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…Previous studies showed that PD173074 inhibits the growth of human RD cells isolated from human muscle tissue ( Gizaw et al, 2022 ), and downregulates FGFR1-mediated p38 phosphorylation induced by Lycium barbarum extract in C2C12 cells ( Meng et al, 2023 ). Similar to these studies, our results indicated that PD173074 inhibits HWSC proliferation via FGFR1-dependent signaling, especially the FRS2/Raf1/ERK pathway ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that PD173074 inhibits the growth of human RD cells isolated from human muscle tissue ( Gizaw et al, 2022 ), and downregulates FGFR1-mediated p38 phosphorylation induced by Lycium barbarum extract in C2C12 cells ( Meng et al, 2023 ). Similar to these studies, our results indicated that PD173074 inhibits HWSC proliferation via FGFR1-dependent signaling, especially the FRS2/Raf1/ERK pathway ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that PD173074 inhibits the growth of human RD cells isolated from human muscle tissue (Gizaw et al, 2022), and downregulates FGFR1-mediated p38 phosphorylation induced by Lycium barbarum extract in C2C12 cells (Meng et al, 2023).…”
Section: Identification Of Key Signaling Pathway Involved In Prolifer...mentioning
confidence: 97%